2020
DOI: 10.1177/0003319720943810
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Platelet to Lymphocyte Ratio and Stable Coronary Artery Disease: Meta-Analysis of Observational Studies

Abstract: Recent studies have reported a relationship between the platelet to lymphocyte ratio (PLR) and acute coronary syndromes. The aim of the present study was to investigate the association between PLR and stable coronary artery disease (CAD). A systematic search was conducted based on electronic databases (Cochrane, PubMed, Elsevier, Medline, and Embase). A total of 14 studies (n = 4,871) were included in the meta-analysis. Compared with the non-CAD group, PLR was significantly higher in CAD group ( P = .002). Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 33 publications
2
24
0
3
Order By: Relevance
“…In this context, several inflammatory biomarkers were not only directly involved in the atherosclerotic lesions but also could predict the risk and mortality from CAD. [2][3][4][5][6] Increased blood neutrophil count and neutrophil to lymphocyte ratio (NLR) have been reported be related with the presence, severity, and outcome of coronary artery stenosis. [7][8][9] There are significant differences in neutrophil count and NLR between males and females, and between premenopause and post-menopause stages in females.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, several inflammatory biomarkers were not only directly involved in the atherosclerotic lesions but also could predict the risk and mortality from CAD. [2][3][4][5][6] Increased blood neutrophil count and neutrophil to lymphocyte ratio (NLR) have been reported be related with the presence, severity, and outcome of coronary artery stenosis. [7][8][9] There are significant differences in neutrophil count and NLR between males and females, and between premenopause and post-menopause stages in females.…”
Section: Introductionmentioning
confidence: 99%
“…The predictive value of other blood parameters, such as lymphocytes, monocytes and high-density lipoprotein cholesterol, for clinical outcomes has been demonstrated in the field of cardiovascular disease [ 30 ]. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been reported to be useful markers to predict poor prognosis in CAD patients [ 2 , 31 ]. It is acknowledged that CAD patients with CHF are at high risk for adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical importance of other parameters composed of complete blood count has been shown in cardiovascular medicine. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been reported to be useful markers to predict poor prognosis in CAD patients [2,31]. Zheng et al [17]showed that PHR was an independent prognostic marker for CAD patients after PCI with better prognostic value than absolute platelet counts or hemoglobin levels.…”
Section: Discussionmentioning
confidence: 99%